2020
DOI: 10.1002/bse.2493
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the drivers of renewable energy investments: The role of behavioral factors

Abstract: The scope of this study is to investigate the main determinants of renewable energy investments in Greece. For this reason, we build an appropriate framework to infer the decision‐making process in the renewable energy sources (RES). The main drivers are then categorized under two groups as economic, and behavioral ones. In the next stage, we rely on binomial (logit and probit) and quantile regression analysis to estimate the impact of these factors on investment decisions towards RES. Our findings indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…This is in support of the findings of other studies (Bag et al. , 2021; Raven and Walrave, 2020; Polemis and Spais, 2020). Such ad-hoc policy interventions hinder the achievement of EGD1 and EGD3.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in support of the findings of other studies (Bag et al. , 2021; Raven and Walrave, 2020; Polemis and Spais, 2020). Such ad-hoc policy interventions hinder the achievement of EGD1 and EGD3.…”
Section: Discussionsupporting
confidence: 93%
“…Our study has found a gap in legislation and policy development on technology adoption and usage with hacking, illegal activities and loss of trust as consequent outcomes (Upadhyay et al, 2021). This is in support of the findings of other studies (Bag et al, 2021;Raven and Walrave, 2020;Polemis and Spais, 2020). Such ad-hoc policy interventions hinder the achievement of EGD1 and EGD3.…”
Section: Role Of Digital Technology In Egdsupporting
confidence: 87%
“…To avoid biased results, we incorporate a set of control variables that were selected in accordance with previous studies (Ghisetti, Marzucchi, & Montresor, 2015; Jové‐Llopis & Segarra‐Blasco, 2018; Polemis & Spais, 2020; Tang, Kreiser, Marino, & Weaver, 2010; Tsai & Liao, 2017) and correspond to “FirmAge,” the age of the company; “Size,” the size of the company represented by the logarithm of the total assets; “CapitalExp,” the intensity of the investment in physical capital with respect to the total sales; “R&D,” the intensity of investment in R + D + i with respect to the total sales; “ForeignSales,” the percentage of sales in international markets; “Leverage,” the financial leverage, that is, the proportion of debt that a company supports compared with its own resources; and “Cash” or fund manoeuvre, representing the company's liquidity. In addition, “Country,” “Year” and “Crisis” are included as control variables.…”
Section: Methodsmentioning
confidence: 99%
“…However, a new area of research is emerging with great potential and, therefore, part of the research potential begins to be migrate to the healthcare services, as is evidenced by the articles of Rais et al (2018) or Ferreira et al (2020), which is bringing Portugal closer to Sweden. In Greece, the research interest is not much different from the Portuguese ones, particularly on the incidence in healthcare services (Chatzakis et al 2018;Grekousis and Liu 2019) and water management services (Alamanos et al 2018;Athanasiou et al 2018); however, we note a strong investment in renewable energy-of the 25 articles published in 2018, 10 of which are related to clean energy (Polemis and Spais 2020;Vlachokostas et al 2020).…”
Section: Quantitative Approachmentioning
confidence: 81%